PENGEMBANGAN PUSAT INFORMASI KARIR BERBASIS WEB: OPTIMALISASI LAYANAN TERHADAP MAHASISWA DAN ALUMNI PGMI UIN SUNAN KALIJAGA - M Saidul Muzakki; Anita Ekantini; Inggit Dyaning Wijayanti (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
Interviews with several PGMI students revealed that they are anxious and uncertain about their plans after graduation. This is due to the limited information they receive about further study and professional teacher programs. Efforts are needed to address these issues. The objectives of this study were: 1) to determine the procedures for developing a web-based career information center, 2) to determine the feasibility of the developed career information center based on expert assessments, and 3) to assess potential user responses to the developed career information center. The research method used was R&D with the 4D model (define, design, develop, and disseminate). Data collection was conducted using a questionnaire instrument to obtain expert validation data and potential user responses. The experts included lecturers with expertise in materials, media, and language. Potential users of this product were students and alumni of the PGMI study program at UIN Sunan Kalijaga Yogyakarta. The web-based career information center was successfully developed using the 4D stages (define, design, develop, and disseminate). Based on the analysis, the developed career information center received an A rating from material, media, and language experts, which is in the excellent category. Based on responses from potential users, the developed career information center received a positive response.